A Congregação Cristã no Brasil numa área de alta vulnerabilidade social no ABC paulista: aspectos de sua tradição e transmissão religiosa - a instituição e os sujeitos - Foerster, Norbert Hans Christoph (2010)
This thesis studies the tradition and religious transmission of the Christian Congregation in Brazil, in an area of ​​greater social vulnerability, from the institution and the subjects. Religious reproduction in contemporary modernity is hampered by the diminished capacity of religious institutions to regulate the beliefs of their faithful, and this capacity is analyzed in the case of the Christian Congregation in Brazil, in a neighborhood of high social vulnerability, on the border between São Bernardo do Field and diadem. The social dimensions of the Christian Congregation in Brazil are studied from a statistical perspective of the Brazilian Pentecostal field. The local social reality is analyzed and the specific peripheral situation of the studied neighborhood is elaborated. An ethnography of the worship of the Christian Congregation provides the data for analysis of the actors in worship, the ritual process, and the function of worship for the articulation of religious identity. Finally, from in-depth interviews and field observation, an ethnography of the members of the Christian Congregation, men and women, in differentiated situations of vulnerability is elaborated. We analyze which social networks, internal to the Christian Congregation in Brazil and external, these members create and to what extent the doctrines and practices of the Congregation, transmitted in the rite, the institutional reproduction device par excellence, can form the subjectivity of its faithful, understood as complex set of perception, affection, thought, desire and fear. (AU)